Commentary & Reflections from the TikTok Methodologies Discussion Forum - Bondy Valdovinos Kaye D.; Southerton Clare; Wang Wei (Cultural Science)
As methodologies for studying TikTok continue to develop, deliberation among research communities can offer valuable insights to incorporate different approaches and iterate on emerging research designs. In July 2021, the TikTok Cultures Research Network held a public research forum on TikTok methodologies that was attended by over two-hundred researchers and members of the public from around the world. The discussion-based event featured two panels and a vibrant open question and answer session that highlighted many of the complex issues that TikTok researchers are facing. In this short piece, the two discussion moderators and one of the event’s organisers reflect on some of the unanswered questions from our forum. Topics that were brought up by researchers in the audience included ethical considerations to protect research participants, particularly younger TikTok users, as well for researchers, particularly when studying problematic or extreme content. Audience members raised technical questions about how to collect and store large quantities of video data or extract and analyse qualitative elements such as video text or hashtags. Audience members also raised questions about how to avoid biases when studying a platform that caters experiences to users’ individual cultural preferences.